Interpretation and application of carbon isotope ratios in freshwater diatom silica. (17th June 2016) - Webb, Megan; Barker, Philip A.; Wynn, Peter M.; Heiri, Oliver; van Hardenbroek, Maarten; Pick, Frances; Russell, James M.; Stott, Andy W.; Leng, Melanie J.
ABSTRACT: Carbon incorporated into diatom frustule walls is protected from degradation enabling analysis for carbon isotope composition (δ 13 Cdiatom ). This presents potential for tracing carbon cycles via a single photosynthetic host with well‐constrained ecophysiology. Improved understanding of environmental processes controlling carbon delivery and assimilation is essential to interpret changes in freshwater δ 13 Cdiatom . Here relationships between water chemistry and δ 13 Cdiatom from contemporary regional data sets are investigated. Modern diatom and water samples were collected from river catchments within England and lake sediments from across Europe. The data suggest dissolved, biogenically produced carbon supplied proportionately to catchment productivity was critical in the rivers and soft water lakes. However, dissolved carbon from calcareous geology overwhelmed the carbon signature in hard water catchments. Both results demonstrate carbon source characteristics were the most important control on δ 13 Cdiatom, with a greater impact than productivity. Application of these principles was made to a sediment record from Lake Tanganyika. δ 13 Cdiatom co‐varied with δ 13 Cbulk through the last glacial and Holocene. This suggests carbon supply was again dominant and exceeded authigenic demand. This first systematic evaluation of contemporary δ 13 Cdiatom controls demonstrates that diatoms have the potential to supply a record of carbon cycling through lake catchments from sediment records over millennial timescales.